2006
DOI: 10.1590/s1516-635x2006000300004
|View full text |Cite
|
Sign up to set email alerts
|

Water intake and digestive metabolism of broilers fed all-vegetable diets containing acidulated soybean soapstock

Abstract: A study was conducted to compare live performance and digestive metabolism of broiler chickens fed all-vegetable diets (All-Veg) compared to a regular diet including animal by-products. Three feeds were formulated and provided to broilers according to the feeding program: pre-starter from 1 to 10 days, starter from 11 to 21 days, and grower from 21 to 35 days. All feeds had corn and soybean meal as major ingredients; however, two of them were all-vegetable diets having either Degummed Soybean Oil (DSO) or Acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…In fact, it was clear that the calculated feed conversion ratios for all groups were exhibited comparable figures. These findings came in consistent with previous reports on rabbits (Beynen, 1988;Ayyat, 1991;Fernandez and Fraga, 1992), chickens (Scaife et al, 1994), cows (Palmquist and Jenkins, 1980;Whitney et al, 2000), fishes (Sener and Yildiz, 2003), and humans (James, 1988), but contradict other reports on chickens (Attia et al, 1994;Soliman et al, 1999;Vieira et al, 2006). It is possible that the disparity between these studies may be attributed to the depressed DM digestibility, insufficiency of metabolizable protein, and low plasma insulin-like growth factor-1 level, as well as to the variation of the dietary vegetable oils, their quality, and the inclusion process or rate.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, it was clear that the calculated feed conversion ratios for all groups were exhibited comparable figures. These findings came in consistent with previous reports on rabbits (Beynen, 1988;Ayyat, 1991;Fernandez and Fraga, 1992), chickens (Scaife et al, 1994), cows (Palmquist and Jenkins, 1980;Whitney et al, 2000), fishes (Sener and Yildiz, 2003), and humans (James, 1988), but contradict other reports on chickens (Attia et al, 1994;Soliman et al, 1999;Vieira et al, 2006). It is possible that the disparity between these studies may be attributed to the depressed DM digestibility, insufficiency of metabolizable protein, and low plasma insulin-like growth factor-1 level, as well as to the variation of the dietary vegetable oils, their quality, and the inclusion process or rate.…”
Section: Discussionsupporting
confidence: 90%
“…One of the substantial advantages is that these vegetable oils are considered a rich source of essentially polyunsaturated fatty acids (PUFA; Baldini et al, 2000;Calvani and Benatti, 2003). In fact, supplying refined vegetable oils to mammalian and birds rations has been observed to have positive effects on growth rate, carcass traits and meat composition (Santoma et al, 1987;Beynen, 1988;Ayyat, 1991;Keteslegers et al, 1995;Soliman et al, 1999;Whitney et al, 2000;Vieira et al, 2006). However, it is not clear what are the subsequent effects of supplementing such oils on the reproductive performance (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…As the dietary potassium and chloride contents decreased from diet 1 to diet 4, a reduced water consumption and higher excreta DM contents were expected (Borges et al., ; Vieira et al., ), with resulting beneficial effects for the foot pad health of the animals. Although a high DM content of the litter is supposed to prevent foot pad dermatitis in broilers (Abd El‐Wahab et al., ; De Jong et al., ), in this study, groups with higher DM contents of excreta and litter were associated with high (= unfavourable) foot pad scores.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, for the studies concentrated on broilers, soapstock supplemented diet does not effect live & carcass weight, feed consumption and feed conversation ratio (Bilal et al 1999(Bilal et al , 2001Vieira et al 2002;Baião and Lara 2005;Vieira et al 2006a). In addition, soapstock supplementation of 6% (Vieira et al 2006b) and 8% (Machado et al 2003) level doesn't have negative impact on broilers. On the other hand, according to Balevi et al (2001), amount of feed consumption and increase in live weight values showed differences and feed consumption was observed the maximum for the group having acidulated soapstock oil and increase in live weight was found to be maximum for the group having crude oil.…”
Section: Discussionmentioning
confidence: 99%